Pengaruh Pelatihan, Pengawasan, dan Disiplin Kerja terhadap Kinerja Karyawan - Faura Zillah; Renny Husniati; Alfida Aziz (Studi Ilmu Manajemen dan Organisasi, 2022)
Purpose: This study aims to analyze the effect of Training, Supervision and Work Discipline on Employee Performance of PT Bank DKI Permata Hijau Branch. Research Methodology: This study uses quantitative research methods, and uses non-probability sampling that uses convenience sampling to take samples from people who are easy to meet. Results: In the partial regression coefficient test, the t-count of the training variables is 2.416, supervision is 2.089, and work discipline is 6.000, all calculations show greater than the t-table calculation of 1.994, meaning that the variables of training, supervision, and work discipline have an effect on employee performance. Limitations: Dissemination of dissemination is not carried out directly to respondents, with the spread of dissemination via google form. Contribution: This research is expected to improve the performance of employees of PT Bank DKI Permata Hijau Branch through training, supervision, and work discipline.